2021
DOI: 10.1027/2151-2604/a000431
|View full text |Cite
|
Sign up to set email alerts
|

Community-Augmented Meta-Analyses (CAMAs) in Psychology

Abstract: Abstract. The limits of static snapshot meta-analyses and the relevance of reproducibility and data accessibility for cumulative meta-analytic research are outlined. A publication format to meet these requirements is presented: Community-augmented meta-analyses (CAMA). We give an overview of existing systems implementing this approach and compare these in terms of scope, technical implementation, data collection and augmentation, data curation, tools available for analysis, and methodological flexibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 39 publications
0
28
0
1
Order By: Relevance
“…A CAMA is supposed to facilitate and foster the accumulation of evidence by providing a user‐friendly infrastructure to the research community. Existing systems in psychology have been reviewed and presented in a previous article 17 . In essence, four systems were compared: The crowdsourced platform Curate Science 18 allows the permanent curation of findings by the research community and enables a systematic evaluation of empirical research, primarily in cognitive and social psychology.…”
Section: Community‐augmented Meta‐analysismentioning
confidence: 99%
“…A CAMA is supposed to facilitate and foster the accumulation of evidence by providing a user‐friendly infrastructure to the research community. Existing systems in psychology have been reviewed and presented in a previous article 17 . In essence, four systems were compared: The crowdsourced platform Curate Science 18 allows the permanent curation of findings by the research community and enables a systematic evaluation of empirical research, primarily in cognitive and social psychology.…”
Section: Community‐augmented Meta‐analysismentioning
confidence: 99%
“…Against the background of an ongoing replication crisis in psychology ( Open Science Collaboration, 2015 ; Świątkowski and Dompnier, 2017 ; Klein et al, 2018 ), we have argued that PLS may be a powerful tool for rebuilding public trust in psychological science, and first experimental findings ( Kerwer et al, 2021 ) seem to support this notion (see also Carvalho et al, 2019 for non-experimental findings that point in the same direction). Because meta-analyses possess a higher quality of evidence and are instrumental for summarizing findings and guiding practitioners ( Borenstein et al, 2009 ; Bastian et al, 2010 ), we further argue that the lay-friendly communication of psychological meta-analytical findings is of particular importance – even though legitimate criticisms on the validity of their findings may exist (e.g., Sharpe and Poets, 2020 ; Burgard et al, 2021 ; Patall, 2021 ).…”
Section: Introductionmentioning
confidence: 94%
“…For this purpose, Study 2 also had two study arms. In study arm A, two PLS with comparably low complexity were presented: One PLS reported only one correlation coefficient as an effect size (based on a meta-analysis by Schwalm et al, 2021 , PLS_LC1), and one PLS reported only one mean difference as an effect size (based on a meta-analysis by Bucher et al, 2020 ; in the ZPID’s PsychOpen CAMA system, see Burgard et al, 2021 , PLS_LC2). Study arm B included two entirely different PLS with comparably high complexity: One PLS reported meta-moderator analyses (based on a meta-analysis by Bergmann and Cristia, 2016 , PLS_HC1), and one PLS reported nine correlation coefficients (based on a meta-analysis by Yule et al, 2019 , PLS_HC2).…”
Section: Studymentioning
confidence: 99%
“…There exist several open science repositories, such as the Open Science Foundation (OSF; for a tutorial, see Soderberg 2018), to preregister and make documents publicly available. Furthermore, several initiatives in the social sciences have been established to develop dynamic metaanalyses, such as metaBUS (Bosco et al 2015(Bosco et al , 2017, MetaLab (Bergmann et al 2018), or PsychOpen CAMA (Burgard et al 2021).…”
Section: Open-science Practicesmentioning
confidence: 99%